Perforin evolved from a gene duplication of MPEG1, followed by a complex pattern of gene gain and loss within Euteleostomi - D’Angelo Michael E; Dunstone Michelle A; Whisstock James C; Trapani Joseph A; Bird Phillip I (BMC Evolutionary Biology, 2012)
Abstract Background The pore-forming protein perforin is central to the granule-exocytosis pathway used by cytotoxic lymphocytes to kill abnormal cells. Although this mechanism of killing is conserved in bony vertebrates, cytotoxic cells are present in other chordates and invertebrates, and their cytotoxic mechanism has not been elucidated. In order to understand the evolution of this pathway, here we characterize the origins and evolution of perforin. Results We identified orthologs and homologs of human perforin in all but one species analysed from Euteleostomi, and present evidence for an earlier ortholog in Gnathostomata but not in more primitive chordates. In placental mammals perforin is a single copy gene, but there are multiple perforin genes in all lineages predating marsupials, except birds. Our comparisons of these many-to-one homologs of human perforin show that they mainly arose from lineage-specific gene duplications in multiple taxa, suggesting acquisition of new roles or different modes of regulation. We also present evidence that perforin arose from duplication of the ancient MPEG1 gene, and that it shares a common ancestor with the functionally related complement proteins. Conclusions The evolution of perforin in vertebrates involved a complex pattern of gene, as well as intron, gain and loss. The primordial perforin gene arose at least 500 million years ago, at around the time that the major histocompatibility complex-T cell receptor antigen recognition system was established. As it is absent from primitive chordates and invertebrates, cytotoxic cells from these lineages must possess a different effector molecule or cytotoxic mechanism.